PERGUMULAN PENGELOLAAN SUMBER DAYA HUTAN DIKOTOMI HUKUM NEGARA DENGAN HUKUM ADAT - Devrayno (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2016)
Forests are one of the country's wealth and resources of the nation, both in terms of the economic aspects of the social aspects of culture and science. Therefore, in the management and utilization of forest resources wisely and sustainably is the trust of the people of Indonesia to achieve the welfare of all people indonesia.Pengelolaan and utilization should be directed to benefit as much as possible for the prosperity of the people to keep the preservation of forest resources. It is the mandate of the people of Indonesia through the constitution that must be implemented by forest managers. However, efforts to increase prosperity through the management of forest resources, especially for forest communities is yet to be felt and the need to gain greater attention. In fact, in the management of forest resources enactment of two legal systems, the law of the State and customary law, where the forest according to the legal aspects of the State is the standing timber to contain the economic value that needs to be exploited on a large scale, while aspects of customary law that the forest is as the residence and the source of life of indigenous peoples living in and around forests. So in the management and beneficiaries occurred dichotomy between countries with legal hukum adat. Kebijakan use and management of forest resources must not only emphasize on technical considerations - economic, but also have to look at the social aspects of culture, law and social welfare. Because in essence State law and customary law made basically have the same philosophical purpose, namely the same as wanting to protect and welfare of all its people.